Sand suspension and fluxes by wave groups and equivalent monochromatic waves. (15th May 2019) - van der Zanden, Joep; van der A, Dominic A.; Thorne, Peter D.; O'Donoghue, Tom; Ribberink, Jan S.
Abstract: Sand transport dynamics under non-breaking regular waves and wave groups are studied in a large-scale wave flume. The water surface elevation, flow velocity, suspended sand concentration (SSC) distributions, and bedforms were measured over a horizontal test section of medium sand. The experiment involved five wave groups that had equal root-mean-square water surface elevation and mean period, but which differed in terms of modulation, wave group length, and short wave sequencing. In addition, three monochromatic wave conditions were generated which were equivalent to the wave groups in terms of root-mean-square water surface elevation or maximum wave height. Temporal and vertical distributions of SSC suggest a more effective sediment pumping for symmetric and backward leaning 'waxing' wave groups. Vertical distributions of the SSC phase lag indicate a more rapid vertical pumping for the short-duration wave group. Overall, the differences between wave group conditions are small and the time-averaged SSC and sediment diffusivity profiles are very similar. The total net suspended sand flux consists of current-related, long-wave-related and short-wave-related contributions that are all of similar magnitude. The net total suspended sand flux was always offshore-directed, but its magnitude depends on the vertical and temporal variation of SSC at short- and long-wave time scales. The results are used to discuss the applicability of the 'equivalent wave concept' for time-averaged SSC distributions and net suspended sand transport. Highlights: Laboratory experiment involving five wave group and three regular wave conditions. Detailed measurements of ripple dimensions and sand suspension are presented. Processes are studied at short-wave, wave group, and time-averaged time scales. Different net suspended sand flux contributions are quantified. The applicability of the equivalent wave concept for grouped waves is discussed.